Enterprise, business-process and information systems modeling 10th International Workshop, BPMDS 2009, and 14th International Conference, EMMSAD 2009, held at CAiSE 2009, Amsterdam, The Netherlands, June 8-9, 2009, proceedings - BPMDS 2009 (Lecture notes in business information processing, 2009)
This book contains the proceedings of two long-standing workshops: The 10th International Workshop on Business Process Modeling, Development and Support, BPMDS 2009, and the 14th International Conference on Exploring Modeling Methods for Systems Analysis and Design, EMMSAD 2009, held in connection with CAiSE 2009 in Amsterdam, The Netherlands, in June 2009. The 17 papers accepted for BPMDS 2009 were carefully reviewed and selected from 32 submissions. The topics addressed by the BPMDS workshop are business and goal-related drivers; model-driven process change; technological drivers and IT services; technological drivers and process mining; and compliance and awareness. Following an extensive review process, 16 papers out of 36 submissions were accepted for EMMSAD 2009. These papers cover the following topics: use of ontologies; UML and MDA; ORM and rule-oriented modeling; goal-oriented modeling; alignment and understandability; enterprise modeling; and patterns and anti-patterns in enterprise modeling. BPMDS 2009 - Towards a BPM success model: an analysis in South African financial services organisations - A conceptual framework for business process Redesign - Supporting change in business process models using pattern-based constraints - Eliciting goals for business process models with non-functional requirements catalogues - A business process-IT alignment method for business intelligence - Analysis and validation of control-flow complexity measures with BPMN process models - Vertical alignment of process models – How can we get there? - Ontology-based description and discovery of business processes - A method for service identification from business process models in a SOA approach - IT capability-based business process design through service-oriented requirements engineering - Minimising lifecycle transitions in service-oriented business processes - Discovering business rules through process mining - Anomaly detection using process mining - Pattern mining in system logs: opportunities for process improvement - Regulatory compliance in information systems research – Literature analysis and research agenda - Actor-driven approach for business process. How to take into account the work environment? - Towards object-aware process management systems: issues, challenges, benefits - EMMSAD 2009 - Supporting ontology-based semantic annotation of business processes with automated suggestions - On the importance of truly ontological distinctions for ontology representation languages: an industrial case study in the domain of oil and gas - UML models engineering from static and dynamic aspects of formal specifications - MDA-based reverse engineering of object oriented code - Integrated quality of models and quality of maps - Masev (Multiagent System Software Engineering Evaluation Framework) - Transactions in ORM - The orchestration of fact-orientation and SBVR - Goal-directed modeling of self-adaptive software architecture A goaleling framework for self-contextualizable software - Security and consistency of IT and business models at credit suisse realized by graph constraints, transformation and integration using algebraic graph theory - Declarative versus imperative process modeling languages: the issue of understandability - The architecture of the ArchiMate language - Enterprise meta modeling methods – Combining a stakeholder-oriented and a causality-based approach - Organizational patterns for B2B environments – Validation and comparison - Anti-patterns as a means of focusing on critical quality aspects in enterprise modeling.